Risk management of patient safety incidents in hospital settings: trends in portuguese scientific production - da Silva, Marculina; Machado , Ana Margarida Ferreira; Ferreira , Iara Rafaela Pinto da Silva; Lima, Mauren Pimentel; Castilho , Amélia Filomena Oliveira Mendes; Macedo , Ana Paula Morais Carvalho; Andolhe, Rafaela (Disciplinarum Scientia | Saúde, 2025)
Introduction: Patient safety is a topic of global relevance, especially with regard to the reporting of safety incidents associated with healthcare practice, considering the potential harm that these incidents can cause to patients. Objective: To identify and analyze evidence from Portuguese scientific publications on the management of safety incident risk in hospital settings. Method: This is a study of trends in Portuguese theses and dissertations, in the form of a narrative literature review, with a search conducted in September and October 2024 in RepositoriUM, the Scientific Repository, Universidade de Coimbra, and in the Repositório Científico de Acesso Aberto de Portugal (RCAAP). The trend referred to in this study is the mapping of Portuguese scientific productions on the subject, defended in master’s and doctoral courses in higher education institutions in the country, which includes quantitative analysis of publications, temporal and thematic overview. Content analysis was used to analyze data extracted from the assessed productions. Results: Of the thousands of publications identified, 44 were selected for full reading, and 24 comprised the final corpus of the study. The main findings were organized into categories that discussed: types and contributing factors to incidents; facilitators and barriers to reporting in the information system; and risk management strategies focused on patient safety, promoting a culture of safety, and reinforcing healthcare professionals’ awareness of reporting in the system. Final considerations: The study analyzed Portuguese scientific publications on risk management and incident reporting, highlighting the relevance of the topic in publications. The need for research to assess the effectiveness of institutional strategies to promote a culture of patient safety through incident reporting in the reporting system was identified.